Effects of induced metabolic alkalosis on prolonged intermittent-sprint performance - Bishop, D.; Claudius, B. (Medicine & Science in Sports & Exercise, 2005)
Purpose: Previous studies have shown that induced metabolic alkalosis, via sodium bicarbonate (NaHCO3) ingestion, can improve short-term, repeated-sprint ability. The purpose of this study was to assess the effects of NaHCO3 ingestion on a prolonged, intermittent-sprint test (IST).